2005
DOI: 10.1098/rspb.2004.3040
|View full text |Cite
|
Sign up to set email alerts
|

The cost of resistance toBacillus thuringiensisvaries with the host plant ofTrichoplusia ni

Abstract: Selection for resistance to insecticides, diseases and parasitoids is assumed to be costly and often requires tradeoffs with reproductive fitness. The costs of resistance, however, are often difficult to measure. Cabbage looper, Trichoplusia ni, a generalist Lepidopteran herbivore, has become highly resistant following the extensive use of the microbial insecticide, Bacillus thuringiensis kurstaki (Bt) in vegetable greenhouses. We compared the growth rate, pupal size and survival of resistant, susceptible and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 50 publications
6
98
0
2
Order By: Relevance
“…2b). Typically, Þtness costs affecting rs individuals are accompanied by lower Þtness for homozygous resistant (rr) individuals (Carriè re et al 2001(Carriè re et al , 2004Bird and Akhurst 2004; Huang et al 2005;Bird and Akhurst 2007), although some studies have reported Þtness costs only affecting rs individuals Wright 2001, Janmaat andMyers 2005). We do not know why a cost affecting only rs individuals was found for SAF97-H4.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…2b). Typically, Þtness costs affecting rs individuals are accompanied by lower Þtness for homozygous resistant (rr) individuals (Carriè re et al 2001(Carriè re et al , 2004Bird and Akhurst 2004; Huang et al 2005;Bird and Akhurst 2007), although some studies have reported Þtness costs only affecting rs individuals Wright 2001, Janmaat andMyers 2005). We do not know why a cost affecting only rs individuals was found for SAF97-H4.…”
Section: Discussionmentioning
confidence: 85%
“…This means that some refuges may be better at delaying pest resistance to Bt than other refuges. For example, the host plant on which an insect feeds can alter both the magnitude and dominance of costs (Shirai et al 1998, Carriè re et al 2005, Janmaat and Myers 2005, Janmaat and Myers 2006, Bird and Akhurst 2007, Raymond et al 2007b). In addition, entomopathogenic viruses and nematodes can magnify costs in some cases (Gassmann et al 2006Raymond et al 2007a).…”
mentioning
confidence: 99%
“…Fitness costs can enhance the effectiveness of refuges to delay resistance (Gassmann et al 2009a, Carriè re et al 2010. Evidence from laboratory experiments suggests that Þtness costs of Bt resistance can be increased by several ecological factors including host plant species (Janmaat andMyers 2005, Bird andAkhurst 2007), density (Raymond et al 2005), entomopathogens (Raymond et al 2007, and competition for mates (Higginson et al 2005). In addition, laboratory selection experiments have demonstrated the value of refuges in delaying resistance to Bt (Tang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, o custo adaptativo associado à resistência às plantas Bt não foi observado, por exemplo, em Busseola fusca (Fuller) (Van Rensburg, 2007), embora tenha sido relatado em outras espécies de Lepidoptera, como Plutella xylostella (L.) (Groeters et al, 1994), Pectinophora gossypiella (Saunders) (Carrière et al, 2001), Trichoplusia ni (Hübner) (Janmaat & Myers, 2005) e Helicoverpa armigera (Hübner) (Akhurst et al, 2003). Uma possível explicação é que, ao longo do tempo, o custo adaptativo pode ser reduzido por evolução subsequente (Coustau et al, 2000).…”
Section: Resultsunclassified